Analisis Isi Soal UAMBN Bahasa Arab Madrasah Aliyah Tahun Pelajaran 2016/2017 dan 2017/2018 - Obi Saepul Bahri (EDUCARE, 2019)
This content analysis aims to analyze the comparison of language learning content found in the UAMBN Arabic language Aliyah Madrasah between the 2016/2017 Academic Year and 2017/2018 Academic Year. The method used in this study is content analysis using a qualitative research approach. This type of research is descriptive research using documentation techniques. From the results of the 2016/2017 problem analysis, researchers found a question of cultural content and a mindset numbering 14 questions, consisting of 8 cultural content and a mindset of 6. The vocabulary content was 4 questions. The structure content is 31 questions. And the content of the terminology is one question, namely the question 43.